Ultrafast high-temperature sintering and thermoelectric properties of n-doped Mg2Si. (9th April 2023) - Boldrini, Stefano; Ferrario, Alberto; Fasolin, Stefano; Miozzo, Alvise; Barison, Simona
Abstract: Ultrafast high-temperature sintering (UHS) is a recently proposed technique able to synthesize and sinter dense materials within seconds. Although UHS has already proved its effectivity with a large set of materials, spanning from refractory ceramics to complex metal alloys, any application to thermoelectric materials is today still lacking. Mg2 Si is a well-established thermoelectric material. It is based on wide available non-critical raw materials, it is non-toxic, lightweight and it expresses its best thermoelectric performances in the intermediate temperature range (up to about 600 °C). Mg2 Si is typically produced with powder processing by Spark Plasma Sintering (SPS), partially limiting its widespread diffusion also due to the costly production technique. Here we present a simple route to sinter Mg2 Si pressed powders by UHS. The process allowed to obtain dense samples (with relative densities >95%) with 20 s heating up to about 1080 °C followed by a rapid free cooling, a total thermal history below 1 min, and with energy demand at the Wh scale. The high process rate proved its efficacy in preventing grain growth and in avoiding any significant Mg evaporation. A full thermoelectric functional characterization is presented for Mg2 Si and Bi-doped Mg2 Si, together with a comparison with SPS-produced properties.